CHALLENGES AND IMPACTS OF DIFFERENTIATED INSTRUCTION IMPLEMENTATION FOR SIXTH-GRADE ELEMENTARY SCHOOL STUDENTS - Barkat, Patimah; Supartinah, Supartinah (Jurnal Visi Ilmu Pendidikan, 2025)
This study aims to analyze the implementation of differentiated learning at SD Negeri 09 Trans Sangat Molo, Bengkayang Regency. Differentiated learning is an approach tailored to students' learning styles, abilities, and interests to improve their motivation, engagement, and learning outcomes. This study used a qualitative approach with a case study method, collecting data through interviews, observations, and documentation studies. The focus of this study was to explore the challenges faced by teachers in implementing differentiated learning and its impact on students. The results showed that differentiated learning successfully increased student motivation and engagement, especially by adapting materials, methods, and assessments to their learning styles. However, the implementation of differentiated learning faced challenges such as limited time, resources, and teacher training. Limited technological devices, limited internet access, and a lack of adequate training for teachers were obstacles to optimal learning implementation. The implementation of differentiated learning is expected to optimize student learning outcomes if supported by adequate resources and more structured teaching strategies. Thus, this study provides important recommendations to overcome the challenges in implementing differentiated learning in schools with diverse students.